1997
DOI: 10.1089/hum.1997.8.8-903
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplant Methotrexate Administration Leads to Improved Curability of Mice Bearing a Mammary Tumor Transplanted with Marrow Transduced with a Mutant Human Dihydrofolate Reductase cDNA

Abstract: To test the concept that protection of bone marrow progenitor cells via introduction of a drug resistance gene would allow larger and curative doses of chemotherapy to be administered, we used mice bearing a transplanted breast cancer as a model system. Mice bearing the E0771 tumor were treated with lethal doses of cyclophosphamide (CPA) and rescued from toxicity by administration of bone marrow transduced with a mutant dihydrofolate reductase (DHFR) cDNA (Ser-31) in a retroviral construct. Animals receiving m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…It was reported that mice transplanted with DHFR -transduced BMCs had evidence of improved curability and reduced drug toxicities to methotrexate (MTX ), an antifolate drug. 8 Trimetrexate and a nucleoside transport inhibitor ( to prevent thymidine rescue ) also showed promising results for in vivo selection in DHFR transplanted mice. 15 However, only modest results were obtained more recently in mice using methotrexate alone as the selective agent.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that mice transplanted with DHFR -transduced BMCs had evidence of improved curability and reduced drug toxicities to methotrexate (MTX ), an antifolate drug. 8 Trimetrexate and a nucleoside transport inhibitor ( to prevent thymidine rescue ) also showed promising results for in vivo selection in DHFR transplanted mice. 15 However, only modest results were obtained more recently in mice using methotrexate alone as the selective agent.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here using the MFG-CD construct clearly demonstrate the feasibility of obtaining in vivo long-term persistence of CD and long-1549 term expression of human CD in hematopoietic cells. We plan to transplant CD transduced marrow cells into tumor-bearing mice to determine if curability with cytosine nucleoside analogues can be obtained using chemoprotection as reported by Zhao et al 24 for the DHFR gene and methotrexate therapy. Future improvements in vectors to increase efficiency of transduction and expression of CD in human hematopoietic cells will facilitate the use of this gene for chemoprotection to increase the therapeutic effectiveness of cytosine nucleoside analogues in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…49 DHFR-transduced hematopoietic cells can be enriched in vivo following administration of antifolates. 50,51 Although taxol selection has been shown to result in enrichment of MDR1-transduced bone marrow cells, 19 …”
Section: Gene Therapymentioning
confidence: 99%